Abuse of patent rights for pharmaceuticals in wartime conditions - A.O. Kodynets; O.F. Doroshenko; I.P. Volynets; G.K. Dorozhko; V.O. Petrenko; V.V. Belitsky (Medičnì Perspektivi)
The article addresses the issue of patent rights abuse in relation to pharmaceuticals during wartime conditions. The aim of the study is to summarize the problems of patent rights abuse in the national legislation, identify ways to resolve them, and formulate conclusions to reduce such abuses. The study employs general scientific and specialized methods of scientific cognition, including dialectical, formal-logical, system-structural, comparative-legal methods, as well as modeling, analysis, and synthesis. Together, these methods facilitated the organization, planning, and execution of the research. The information search covered the period from 2001 to 2024. The study is based on scientific publications from databases and search engines (PubMed, JAMA, Scopus, Springer, BMC, Oxford Academic, Cairn.info), international and domestic legal acts, statistical studies of international organizations (Precedence Research, Statista, Proxima Research), patents on inventions related to pharmaceuticals, court rulings, and the recommendations of international and domestic experts. The inclusion criteria for materials were scientific articles, legal acts, court rulings, and analytical reviews related to pharmaceutical patent rights, patent monopoly abuses, "evergreening" patents, and unfair competition in the pharmaceutical industry. The following search queries were used: "abuse of patent rights on pharmaceuticals," "patent monopoly in the pharmaceutical industry," "evergreening patents," "unfair competition in the pharmaceutical market," and "intellectual property in wartime conditions." Exclusion criteria included sources unrelated to the legal regulation of pharmaceutical patents, materials not directly connected with patent rights, and publications that did not meet scientific standards and credibility. It has been determined that patent monopolies can lead to higher drug prices, the prevention of generic drug production, import dependency, reduced competitiveness, and other consequences. Additionally, the creation of "evergreening" patents affects competitive relations, representing a form of unfair competition. Examples of patent monopolies in pharmaceuticals owned by major global pharmaceutical companies (Gilead, Merck Sharp & Dohme Corp., etc.) were examined. Attention is drawn to the problematic aspects of legislative implementation to strengthen the protection of individuals’ interests in the field of intellectual property during martial law, which leads to misinterpretation and implementation of relevant provisions and requires updating. Court cases of pharmaceutical companies regarding the artificial maintenance of patent monopolies and the blocking of generic drugs entering the Ukrainian market were analyzed. The need for updating and improving the legislative mechanism for regulating the validity of invention patents has been emphasized.